Pengaruh Sosial Media Terhadap Peningkatan Minat Berkunjung Wisatawan Di Atv Aja - Maulida, Helmalia; Hasna Nabila Zulfa; Ramayani Yusuf (Universitas Haji Sumatera Utara, 2024)
AbstractThis scholarly investigation delves into the profound influence of social media on the escalating attraction of tourists to ATV Aja, a renowned tourist spot. The research delves into the intricate interplay between diverse social media platforms and the upsurge in interest and aspiration to partake in the distinctive offerings of ATV Aja tourism. Through a comprehensive examination of different social media channels and their impact, the study endeavors to furnish insightful perspectives into the pivotal role played by social media in molding tourists' perspectives and choices pertaining to travel and adventurous pursuits.Keywords: Social Media, Interest in Visiting, ATV Aja